Screening for anticoagulation undertreatment in more than 100, 000 patients with atrial fibrillation in general practices in the Netherlands. (14th October 2021) - Voorhout, L.J; Pisters, R; Geurts, C.H.P.H; Oostindjer, A; Van Doorn, S; Rila, H; Fuijkschot, W.W; Hemels, M.E
Abstract: Background and aim: Atrial fibrillation (AF) is associated with a significant morbidity and increased mortality risk, predominantly due to risk of stroke and thromboembolism. Despite availability of highly effective and practical oral anticoagulation (OAC) guidelines recommended therapy is often underutilized. Therefore, we investigated the underuse of OAC in individual AF patients through on-demand screening of general practices (GPs) across the Netherlands. Methods: We performed a multi-center, cross-sectional study in 39 GPs. Using electronic patient files, we were able to screen the entire GP population for AF, CHA2DS2-VASc scores, and the use of guidelines recommended OAC. In case of OAC undertreatment we checked for any documented reason. Additionally, six weeks following the screening we asked all GPs to provide information on actions taken for the undertreated patients. Results: In total 101, 207 patients records were screened identifying 2, 375 non-valvular AF patients with a mean CHA2DS2-VASc score of 3.2. OAC use consisted of direct oral anticoagulants in 1, 342/1, 984 (68%) and vitamin K antagonists in the remainder of patients. OAC undertreatment was present in 92/1001 (9, 2%) males and 102/1374 (7, 4%) in females, respectively. Figure 1 shows the GP patient population with AF, divided into groups by CHA2DS2-VASc score and their corresponding antithrombotic therapies. Reasons to withhold OAC were patient refusal (n=10), cardiologist advice (n=7), high risk of bleeding (n=7), and terminal illness (n=4). In 159/194 (82%) patients no reason was reported. Data regarding actions following the identification of OAC undertreatment was available in 29 practices representing 92/194 (47%) of the OAC undertreatment cases. After consultation OAC was initiated in 9/92 (10%) only. Conclusions: In this large Dutch study among GPs we observe 8.2% undertreatment of OAC in AF patients. More males than females were undertreated as were those with the highest CHA2DS2-VASc scores. Only in a small minority of cases detection of OAC undertreatment lead to OAC initiation. This highlights the need to improve awareness and communication of OAC treatment aimed at preventing strokes. Funding Acknowledgement: Type of funding sources: None.